Analysis of Key Aroma Compounds in Fermented Goji Berry Wine - LIU Yaran, LI Junlong, GU Peishan, LI Ruotong, ZHU Baoqing, ZHANG Bolin (Shipin Kexue, 2024)
The volatile aroma compounds of wine fermented from goji berries were evaluated by liquid-liquid extraction-solvent-assisted evaporation-gas chromatography-mass spectrometry-olfactometry (LLE-SAFE-GC-MS-O) combined with GC-quadrupole-MS (GC-qMS) and GC-Orbitrap-MS. The key aroma compounds were identified by aroma reconstitution and quantitative descriptive sensory analysis. The results showed that ethyl esters (ethyl cinnamate, ethyl acetate, ethyl 2-methylpropanoate, ethyl 2-methylbutanoate, ethyl 3-methylbutanoate, ethyl hexanoate, ethyl lactate, ethyl octanoate, and ethyl decanoate), other esters (isoamyl acetate and isoamyl lactate), C13-norisoprenoids (β-damascenone and β-ionone), volatile phenols (4-ethylguaiacol, eugenol, 2,4-di-t-butylphenol), alcohols (1-octen-3-ol, benzyl alcohol, phenylethyl alcohol and isopentyl alcohol) and other compounds (naphthalene, methionol, octanoic acid and 2-acetylpyrrole) contributed the major aroma attributes of goji berry wine. This finding will help to enrich and improve the theoretical basis of the aroma of goji berry wine and lay the foundation for aroma enhancement and quality improvement of goji berry wine.